Proceedings of the Proceedings of the 2nd International Conference on Language, Literature and Education, ICLLE 2019, 22-23 Aug 2019
DOI: 10.4108/eai.19-7-2019.2289474
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Arabic Language Teaching Based on Error Analysis Theory

Abstract: Islamic Boarding School is an Indonesian Islamic education institution that has great attention to learning Arabic. To improve student language, this institution teach composition systematically in the Insya' lessons. However, the Institute continues to face considerable difficulties in learning the Arabic language. Those difficulties appear in the high frequency of errors in the structure of Arabic Sentence. The purpose of this study was to design the Student Worksheet materials based on linguistic error anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Punctuation errors, such as commas or periods, can affect sentence comprehension. Meanwhile, writing style analysis involves assessing whether the writer's style is appropriate for the context and purpose of the communication (Zaid et al, 2019). The importance of language error analysis lies in the effort to improve the quality of communication.…”
Section: Results and Discussion Language Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Punctuation errors, such as commas or periods, can affect sentence comprehension. Meanwhile, writing style analysis involves assessing whether the writer's style is appropriate for the context and purpose of the communication (Zaid et al, 2019). The importance of language error analysis lies in the effort to improve the quality of communication.…”
Section: Results and Discussion Language Error Analysismentioning
confidence: 99%
“…This process not only helps improve linguistic proficiency but also increases understanding of Arabic culture and the richness of the Arabic language. Errors in Arabic are a natural part of learning, and their analysis is essential for better mastery of the language (Zaid et al, 2019). The error analysis referred to in this study is to discover students' mistakes in pronouncing Arabic words in hiwār that do not follow the rules of makhārij al-hurūf.…”
Section: Arabic Language Error Analysismentioning
confidence: 99%
“…The findings demonstrated that using storytelling to teach speaking might encourage students to communicate in English, regardless of how poorly their language skills were, and to express their views freely. (Zaid & Sarjiyati, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Wulandari (2020) also reported that the difficulties in pronouncing similar letters in speaking Arabic were often faced by students who came from non-Arabic speakers. Zaid et al, (2019) reported that word and phrase errors in the form of substitution, addition and omission are also the biggest obstacles in learning Arabic. Adila (2019) and Khuwaileh and Shoumali (2000) argue that the most grammatical errors occur in the process of writing Arabic.…”
Section: Introductionmentioning
confidence: 99%